PERFORMANCE FACTORS OF GUIDANCE TEACHERS/COUNSELORS - Retnaningdyastuti, Sri Rejeki; Sugiharto, DYP; Widodo, Tri; Widodo, Joko (Universitas Negeri Semarang, 2013)
The objectives of this study are to analyze to what extent the factors affect the performanceof guidance teachers/counselors and to find the factors that greatly influencethe performance of guidance teachers/ counselors. The population consistedof 239 guidance teachers/counselors of Junior High Schools in Semarang. Thesample consisted of 200 guidance teachers/ counselors, selected by using a proportionalrandom sampling technique. The data were collected by using closed selfassessmentquestionnaires. The result of the try-out of the questionnaires showedthat 144 items were valid and reliable. Structural Equation Modeling Applications(SEM) through LISREL was used to analyze the data. The findings showed that 1)pedagogical competence, work motivation, supervision and school culture affectthe performance of the guidance teachers or counselors, and 2) pedagogical competenceand school culture have great effect on the performance of the guidanceteachers/counselors